You are on page 1of 7

Different kinds of Mathematical Induction

(1) Mathematical Induction


Given

A N,

[1A

(aA a+1A)]

A = N.

(2) (First) Principle of Mathematical Induction


Let P(x) be a proposition (open sentence), if we put
A = {x : x N
If

p(x) is true} in (1), we get the Principle of Mathematical Induction.

(1) P(1) is true;

(2) P(k) is true for some k N P(k+1) is true


then
P(n) is true n N.
(3) Second Principle of Mathematical Induction
If

(1) P(1) is true;


(2) 1 i k, P(i) is true

[i.e. P(1) P(2) . P(k) is true]

P(k+1) is true
then

P(n) is true n N.

(4) Second Principle of Mathematical Induction (variation)


If

(1) P(1) P(2)


(2) P(k-1) P(k)

then

is true;
is true for some

k N\{1} P(k+1) is true

P(n) is true n N.

(5) Second Principle of Mathematical Induction (variation)


If

(1) P(1) P(2) . P(m)


(2) P(k)

then

is true for some

is true;

k N P(k+m) is true

P(n) is true n N.

(6) Odd-even M.I.


If

(1) P(1) P(2)


(2) P(k)

then

is true;

is true for some

k N P(k+2) is true

P(n) is true n N.

Page

More difficult types of Mathematical Induction


(7) Backward M.I.

If

(1) P(n) is true n A, where A is an infinite subset of N;


kN

(2) P(k) is true for some


then

P(k1) is true

P(n) is true n N.

(8) Backward M.I. (variation) (more easily applied than (7))

If

(1) P(1) is true;


k N P(2k+1) is true;

(2) P(2k) is true for some

kN

(3) P(k) is true for some


then

P(k1) is true

P(n) is true n N.

(9) Different starting point

If

(1) P(a) is true, where a N;


k N, where k a

(2) P(k) is true for some


then

P(k+1) is true

P(n) is true n N\{1, 2, ., a 1 }.

(10) Spiral M.I.

If

(1) P(1) is true;


k N Q(k) is true

(2) P(k) is true for some

k N P(k+1) is true

Q(k) is true for some


then

P(n) , Q(n) are true n N.

(11) Double M.I.


Double M.I. involves a proposition P(m, n) with two variables m, n.

If

(1) P(m, 1) and P(1, n)

is true m, n N;

(2) P(m+1, n) and P(m, n+1) are true for some


P(m+1, n+1) is true
then

P(m, n)

is true m, n N.
Page

m, n N

A Prime Number Theorem

[Second Principle of Mathematical Induction]

p n < 22 .
n

Prove that the nth prime number


Solution

p n < 22 .
n

Let

P(n)

be the proposition :

For

P(1),

p1 = 2 < 2 2

Assume

P(i)

is true

P(1)

is true.

p1 < 2 2 , p 2 < 2 2 ,..., p k < 2 2 . (*)


1

s.t. 1 i k , i.e.

p1p 2 ....p k < 2 2 2 2 ....2 2


1

For

P(k + 1),

Multiply all inequalities in (*),

p1p 2 ....p k + 1 2 2 2 2 ....2 2 = 2 2 +2 +....+2 = 2 2


1

For any prime factor

Since p1, p2 , ., pk

p k +1 p < 2 2

of

k +1

Let

{an}

P(k + 1)

< 22

k +1

p < 22

k +1

is true.
P(n)

is true n

[Second Principle of Mathematical Induction]

be a sequence of real numbers satisfying


n-1

an = 2

Prove that

p1p 2 ....p k + 1 , we have pk < p and hence pk+1 p.

By the Second Principle of Mathematical Induction,


Recurrive formula

k +1

p1p 2 ....p k + 1 , we have

are not prime factor of

a1 = 2, a2 = 3

and an+2 = 3an+1 2an .

+1.

Solution
Let

P(n)

For

P(1) P(2),

Assume
i.e.

be the proposition :

a1 = 2 = 21-1 + 1,

ak = 2k-1 + 1
ak+1 = 2 + 1
P(k+2),

a2 = 2 = 22-1 + 1 .

P(k) P(k+1) is true for some


k

For

an = 2n-1 + 1 .

(1)

(2)

is true.

By the Second Principle of Mathematical Induction,


Odd Even Mathematical Induction
Let

a1 = 2,

Prove that

a2 = 2

an =

P(1) P(2)

= 3ak+1 2ak = 3(2k + 1) 2(2k-1 + 1) = 2k+1 + 1

ak+2

P(k + 2)

an+2 = an + 1

1
(n + 1) + 1 1 + ( 1)n
2
4

].

Solution

Page

P(n)

is true n

is true.

Let P(n) be the proposition :

an =

1
(n + 1) + 1 1 + ( 1)n
2
4

For P(1),

a1 = 1 =

1
(1 + 1) + 1 1 + ( 1)1
2
4

For P(2),

a2 =1 =

1
(2 + 1) + 1 1 + ( 1)2
2
4

Assume

P(k) is true for some

].

i.e. a k =

P(1) P(2) is true.

1
(k + 1) + 1 1 + ( 1)k
2
4

(*)

For P(k + 2),


ak+2 = ak + 1 =
=

1
(k + 1) + 1 1 + ( 1)k + 1
2
4

1
[(k + 1) + 1] + 1 1 + ( 1)k +1
2
4

, by (*)

P(k + 2) is true.

By the Principle of Mathematical Induction,

P(n) is true n

Backward Mathematical Induction

x + x2
Let f(x) be a convex function defined on [a, b], i.e. f ( x 1 ) + f ( x 2 ) 2f 1
for all x1, x2 [a, b].
2
For each positive integer n, consider the statement:
x + ... + x n
I(n) : If xi [a, b], i = 1, 2, , n, then f ( x 1 ) + ... + f ( x n ) nf 1
.

n
(a)

Prove by induction that I(2k) is true for every positive integer k.

(b)

Prove that if I(n)

(c)

Prove that I(n) is true for every positive integer n.

(n 2) is true, then I(n-1) is true.

Solution
(a)

x + ... + x n
I(n) : If xi [a, b], i = 1, 2, , n, then f ( x 1 ) + ... + f ( x n ) nf 1

n
For I(21), since it is given that

Assume

I(2k)

x + x2
f ( x 1 ) + f ( x 2 ) 2f 1
.
2

I(21)

x 1 + ... + x 2 k
is true. i.e. f ( x 1 ) + ... + f ( x 2k ) 2 k f

2k

is true.

.(1)

For I(2k+1),
f ( x 1 ) + ... + f ( x 2k ) + f ( x 2k +1 ) + ... + f ( x 2k +1 )
x k + ... + x 2k +1
x + ... + x 2k x 2k +1 + ... + x 2k +1
x 1 + ... + x 2k
k
k 1
2k f
+ 2 f 2 +1 k
= 2 f
+ f
k
2
2
2k
2k



x 1 + ... + x 2k x 2k +1 + ... + x 2k +1
= 2 k f
+ f
2k
2k


x 1 + ... + x 2k + x 2k +1 + ... + x 2k +1
= 2 k +1 f
2 k +1

1 x 1 + ... + x 2k x 2k +1 + ... + x 2k +1
+
2 k 2 f
, by I(2)
2k
2k
2

Page

, by (1)

I(2k+1)

is true

(b)

I(n) is true (n 2),

Assume
i.e.

x + ... + x n
f ( x 1 ) + ... + f ( x n ) nf 1

Put

xn =

x 1 + ... + x n 1
n 1

n 1 x 1 + ... + x n 1
+ n
= nf

n
n 1
n 1

, then

x + ... + x n 1
x 1 + ... + x n 1
f ( x 1 ) + ... + f ( x n 1 ) + f 1
nf

n 1
n 1
x + ... + x n 1
f ( x 1 ) + ... + f ( x n 1 ) ( n 1)f 1

n 1
(c)

n ,

(k

and r ) such that

I(n 1) is also true.


n = 2k r.

Spiral Mathematical Induction

Given a sequence {an}

(
(

)
)

2
S 2 m 1 = 2 m 4m 3m + 1

1
S 2 m = m 4m 2 + 3m + 1
2

S n = a i , prove that

Let

a2m-1= 3m(m 1) + 1 and a2m = 3m2,

satisfying

i =1

where

....(1)
....(2)

Solution

Let

For

P(m)

be the proposition :

S2 m 1 =

Q(m)

be the proposition :

S2m =

S1 = a1 = 1

P(1),

Assume

P(k)

is true for some

For

Q(k), S2k = S2k-1 + a2k =

(b)

For

P(k + 1),
S2k+1 = S2k + a2k+1 =

Since

Since

1
m 4m 2 + 3m + 1
2

(1)

is true for

., i.e. S 2 k 1 =

(a)

1
m 4m 2 3m + 1
2

m=1.

1
k 4k 2 3k + 1
2

1
1
k 4k 2 3k + 1 + 3k 2 = k 4k 2 + 3k + 1 .
2
2

(*)

Q(k)

P(k + 1) is true.

is true.

1
k 4k 2 + 3k + 1 + [3(k + 1)k + 1]
2

[(

) (

1
4k 3 + 12k 2 + 12k + 4 3k 2 + 6k + 3 + (k + 1)
2

1
1
3
2
2
4(k + 1) 3(k + 1) + (k + 1) = (k + 1) 4(k + 1) 3(k + 1) + 1 .
2
2

(1)

P(1) is true.

(2)

P(k) is true

By the Principle of Mathematical Induction,

(1)

P(1) is true.

(2)

Q(k)

By the Principle of Mathematical Induction,

is true

Q(k)

Q(1)

is true

P(k + 1) is true

P(n) is true n

is true
P(k + 1) is true

Page

Q(k + 1) is true

Q(n) is true n

Mathematical Induction with parameter

Let

, when a = 1
1
f(a, 1) =
.
0 , when a > 1, a N

and

f (a , n ) + 1
, when a = 1

f(a, n+1) =
.
f (a, n ) + f (a 1, n ) , when a > 1, a N

f (a , n ) =

Prove that

n (n 1)...(n a + 1)
a!

Solution

Let P(n) be the proposition : f (a , n ) =


(1)

(2)

For

n (n 1)...(n a + 1)
a!

P(1), there are two cases:

When a = 1, L.H.S. = f(1, 1) = 1.

R.H.S. =

1
=1
1!

When a > 1,

L.H.S. = f(a, 1) = 0.

R.H.S. =

1(n 1)...(1 a + 1)
=0 .
a!

Assume

is true for some

For

P(k)

., i.e.

When a > 1,

k (k 1)...(k a + 1)
a!

is true.

(2)

k
k +1
+1 = k +1 =
= R.H.S.
1!
1!

L.H.S. = f(a,k) +f(a 1, k)


=

k (k 1)...(k a + 1) k (k 1)...(k a + 2)
+
, by (2), f(a,k) and f(a 1, k) hold .
(a 1) !
a!

k (k 1)...(k a + 2)
[(k a + 1) + a ]
a!

Comment

f (a , k ) =

P(1)

P(k + 1), there are also two cases:

When a = 1, L.H.S. = f(a, k + 1) = f(a, k) + 1 =

(1)

(k + 1)k (k 1)...(k a + 2)
a!

= R.H.S.

P(k + 1) is true.

By the Principle of Mathematical Induction,

If the proposition with natural number

P(n) is true n

n contains a parameter

mathematical induction for all values of a .

Page

a , then we need to apply

Double Mathematical Induction

Prove that the number of non-negative integral solution sets of the equation
x1 + x2 + + xm = n
is

f(m, n) =

m,n

(n + m 1) !
n !(m 1) !

(1)

Solution

Let P(m, n)
(a)

For
In

be the given proposition.

P(1, n), The only non-negative integral solution set of the equation
(1) , f(1, n) =

(n + 1 1) ! = 1
n !(1 1) !

P(1, n) is true .

For

P(m, 1),

x1 = n is only itself .

The non-negative integral solution sets of the equation

x1 + x2 + + xm = 1
are

(1, 0, 0 , 0) , (0, 1, 0, ) , , (0, 0, 0, , 1) .

There are m sets of solution altogether.


In (1),

(b)

f(m, 1) =

P(m, 1)

Assume

(1 + m 1) ! = m
1!(m 1) !

is true .

P(m, n+1) and P(m + 1, n)

m,n

are true for some

. . i.e

the number of non-negative integral solution sets of the equations :

are
For

x1 + x2 + + xm = n +1

(2)

x1 + x2 + + xm + xm+1 = n

(3)

f(m, n+1) =
P(m+1, n+1),

(n + m ) !
(n + 1) !(m 1) !

and

f(m+1, n) =

(n + m ) !

respectively .

n !m !

The non-negative integral solution sets of the equation :

x1 + x2 + + xm + xm+1 = n + 1

(4)

may be divided into two parts : xm+1 = 0 or xm+1 > 0 .


(i)

For

xm+1 = 0 , equation (4) becomes equation (2), and the number of non-negative integral solution
sets is

(ii)

For

f(m, n+1) =

(n + m ) !
(n + 1) !(m 1) !

xm+1 > 0 , replace xm+1 by xm+1 + 1 and equation (4) becomes:


x1 + x2 + + xm + xm+1 = n , and the number of non-negative integral solution
sets is

f(m+1, n) =

(n + m ) !
n !m !

The total number of non-negative integral solution sets is

(n + m ) ! + (n + m ) !
(n + 1) !(m 1) ! n !m !

(n + m ) ! [(n + 1) + m] = [(n + 1) + (m + 1) 1]
(n + 1) !m !
(n + 1) ![(m + 1) 1]!

P(m+1, n+1) is also true .

By the Principle of Mathematical Induction,

Page

P(m, n)

is true m, n